Pengaruh Kualitas Laporan Keuangan, Debt Maturity, Leverage, dan Kinerja Profitabilitas Terhadap Efisiensi Investasi - Dewi, Ovi Rishita; Askandar, Noor Shodiq; Hidayati, Irma (Universitas Islam Malang, 2024)
This study aims to determine the effect of the quality of financial statements, debt maturity, leverage, and profitability performance on investment efficiency in companies. The financial reports used in this quantitative study were sourced from secondary data sources and were obtained via the Indonesia Stock Exchange's (IDX) official website www.idx.co.id. Sampling in this study used a purposive sampling method. The population in this study are manufacturing companies listed on the 2020-2022. The results show that the quality of financial reports, debt maturity, leverage, profitability performance affect investment efficiency, financial report quality and profitability performance has a positive effect on investment efficiency, but the debt maturity and leverage has no effect on investment efficiency.Keywords: Quality of financial reports, debt maturity, leverage, profitability performance,, investment efficiency